DIGITAL TECHNOLOGIES AND THEIR SIGNIFICANCE IN THE FIELD OF WATER MANAGEMENT IN THE CONDITIONS OF DIGITALIZATION OF THE ECONOMY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The article aims to highlight digital technologies and their importance in the use of water resources. Technical solutions for monitoring the condition of agricultural lands and how to monitor them are shown. It is especially useful to learn about modern electronic devices.